The Political and Legal Status of Constitutional Preambles: A Case Study - Fawzi Abukhwait, Assist. Lect. Zahraa (Basra studies journal, 2025)
The constitution constitutes the foundational framework upon which the legal system is built, providing the legislator with essential principles that guide the functioning of the state. Through its constitutional provisions, the constitution sets clear standards that define and clarify numerous fundamental matters. Within this context, constitutional preambles have acquired significant importance, prompting constitutional drafting committees to articulate in them lofty objectives and overarching national aspirations. Constitutional preambles encompass a wide range of themes: some emphasize historical pride, others recount struggles against tyranny, while some highlight national identity, human dignity, or the nature of the political system. Therefore, their content is not limited to what is traditionally expected in preambles. Two major approaches have emerged regarding the legal value of constitutional preambles: one denies any binding legal effect, while the other affirms their interpretive and sometimes normative significance. Despite these differing views, many constitutions reflect the content of their preambles within their operative articles, where the constitutional text often serves as a substantive extension and practical manifestation of the principles introduced in the preamble. These relationships and models will be examined throughout the study.